A modified kinematic hardening model considering hetero-deformation induced hardening for bimodal structure based on crystal plasticity. (1st February 2021) - Zhang, Yong; Chen, Hao; Jia, Yun-Fei; Li, Dong-Feng; Yuan, Guang-Jian; Zhang, Xian-Cheng; Tu, Shan-Tung
Highlights: Modify kinematic hardening model to quantify the hetero-deformation induced hardening. Non-unified Hall-Petch parameters lower the error of predicted yield stress. Contribution of HDI hardening to mechanical properties is clarified. Effect of hardening induced by different bimodal microstructures is analyzed. Abstract: Heterogeneous structures (HS) have been reported to overcome the longstanding challenge of the trade-off between strength and ductility in metallic materials. The deformation incompatibility between the fine grains (FG) and coarse grains (CG), producing hetero-deformation induced (HDI) hardening, is the primary mechanism for superior mechanical properties of HS. In this paper, a kinematic hardening law within the framework of crystal plasticity is modified to quantify the HDI hardening of HS in which a new parameter is established to consider the strength mismatch between FG and CG. Taking bimodal structure (BS) as an example of HS, the good agreement between the experimental and numerical results show that the proposed model can successively predict the mechanical properties, including the evolution of back stress, yield strength and strain hardening of BS with various grain size distributions. Furthermore, the underlying strengthening mechanisms are revealed by switching the HDI hardening term and analyzing the partitioning of the strain and stress in different components of BS. By manipulating the grain size ratio of BS, it is found that the effect of HDI hardening is more sensitive to the size of FG than that of CG. The proposed hardening law can provide a significant guide for heterogeneous material design. Graphical abstract: The figure shows the comparison between simulation results and experimental data (a), the effect of the hetero-deformation induced (HDI) hardening on the flow stress of two components of bimodal structure (b), accumulated plastic strain distribution at different strains (c), and a three-dimensional histogram of hetero-deformation induced hardening distribution for bimodal structure with various grain sizes (d). Image, graphical abstract